COP30 CHALLENGES: WHERE ARE EMPLOYMENT AND INCOME IN THE BRAZILIAN BIOECONOMY (2011–2021) - Geraldo Nascimento da Paz, Edson; Madeira Nogueira, Jorge (RP3 - Revista de Pesquisa em Políticas Públicas, 2025)
Abstract This article addresses the lack of comparable metrics to guide analysis of the bioeconomy in Brazil, a topic that has been treated as a driver of development and climate change but lacks comparable metrics to guide policies and investments. This article aims to measure and characterize the 100% BIO core using microdata from the RAIS (2011–2021) based on two indicators: the core's share of formal employment and its share of the wage bill. This is a quantitative-descriptive study, with sectoral (CNAE) and territorial breakdowns and an assessment of the temporal evolution of these indicators. The results show stability in the share of formal employment at a constant level and a similar share of the wage bill, with a slight increase at the end of the series. Behind this average stability, spatial reconfiguration is observed, with relative gains in the Central-West and South regions, associated with agro-industrial densification, and a loss of traction of traditional primary complexes in states in the Southeast and Northeast. At the sectoral level, the transformation links linked to biomass stand out, such as food and beverage processing, slaughter and dairy, and the pulp and paper chain. In new agricultural fronts, formal employment remained resilient in the 2020–2021 biennium, but gaps persist between employment and income participation where local processing is incipient. In light of these findings, the two indicators used allow prioritizing territories and monitoring initiatives by revealing where the 100% BIO core generates not only formal jobs but also a greater share of income. The study's contribution is to offer standardized and replicable measurement with administrative data, enabling sectoral and territorial comparisons and continuous monitoring of the Brazilian bioeconomy.